THE ROLE OF CORPORATE GOVERNANCE IN REDUCING TAX RISKS AND ACHIEVING SUSTAINABLE DEVELOPMENT-AN APPLIED STUDY IN THE GENERAL TAX AUTHORITY -DIWANIYAH BRANCH - Hayder Oudah Kadhim; Shaymaa Abdulhusein Abdulkadhim Alisawi; Abbas Hadi Abboud (Galaxy International Interdisciplinary Research Journal, 2024)
The research aims to address the theoretical framework of corporate governance in terms of its concept, importance, internal and external mechanisms, as well as clarifying its role in reducing tax risks and working to achieve sustainable development. The research was applied in the Iraqi General Tax Authority / Al-Diwaniyah branch for the data for the fiscal year ending on 12/31/2021. In order to achieve the objectives of the research, a questionnaire was designed in addition to the use of a set of appropriate statistical methods. The study produced a number of findings, the most significant of which were that tax risks—tax evasion being the primary one—can be mitigated by corporate governance, and that corporate governance facilitates sustainable development in a way that complies with business environment standards.